K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

14 tháng 10 2022

\(=\left(sin^2a+cos^2a\right)^3-3sin^2a\cdot cos^2a\cdot\left(sin^2a+cos^2a\right)+3sin^2a\cdot cos^2a\)

=1

19 tháng 8 2021

\(=\frac{\sin^2a}{\sin a-\cos a}-\frac{\sin a+\cos a}{\frac{\sin^2a}{\cos^2a}-1}=\)

\(=\frac{\sin^2a}{\sin a-\cos a}-\frac{\cos^2a\left(\sin a+\cos a\right)}{\sin^2a-\cos^2a}=\)

\(=\frac{\sin^2a\left(\sin a+\cos a\right)-\cos^2a\left(\sin a+\cos a\right)}{\sin^2a-\cos^2a}=\)

\(=\frac{\left(\sin a+\cos a\right)\left(\sin^2a-\cos^2a\right)}{\sin^2a-\cos^2a}=\sin a+\cos a\left(dpcm\right)\)

15 tháng 7 2015

A = (sin2a + cos2a)3 - 3sin2a. cos2a.(sin2a + cos2a) + 3sin2a.cos2a = 1 - 3sin2a. cos2a + 3sin2a. cos2a = 1

a: \(M=\dfrac{1}{tana+cota}=1:\left(\dfrac{sina}{cosa}+\dfrac{cosa}{sina}\right)\)

\(=1:\dfrac{sin^2a+cos^2a}{cosa\cdot sina}=cosa\cdot sina=\dfrac{2\sqrt{2}}{9}\)

b: \(A=\left(sin^2a+cos^2a\right)^3-3\cdot sin^2a\cdot cos^2a+3\cdot sin^2a\cdot cos^2a\)

=1